Socio-ecological dynamics and community ecotourism: A comparative analysis in the guayabero-guaviare river axis (2018)
The effects of the ecotourism in the relationships between inhabitants and their environment are complex and multidimensional. To explore these effects, two community ecotourism initiatives in the Guaviare Province were comparatively analyzed. This territory has been historically affected by the armed conflict and today is given priority as a scenery for the peace construction. The analysis herein articulates approaches both from the political ecology and the socio-ecological systems and considers how important it is to understand the power relations emerging in community ecotourism contexts that, in turn, help to measure how this kind of tourism impacts the socio-ecological dynamics and the strategies by the peasant families who try to diversify their economies to made them sustainable. © 2018, Pontificia Universidad Javeriana. All rights reserved.